Rich Indians : Native People and the Problem of Wealth in American History - Harmon, Alexandra, 1945- (Book collections on Project MUSE., 2010)
Long before lucrative tribal casinos sparked controversy, Native Americans amassed other wealth that provoked intense debate about the desirability, morality, and compatibility of Indian and non-Indian economic practices. Blending social, cultural, and economic history, Alexandra Harmon examines seven such instances of Indian affluence and the dilemmas they presented both for Native Americans and for Euro-Americans--dilemmas rooted in the colonial origins of the modern American economy.